The financial deepening-productivity nexus in China: 1987 - 2001 - Jun Zhang; Guanghua Wan; Yu Jin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The financial intermediation-growth nexus is a widely studied topic in the literature of development economics. Deepening financial intermediation may promote economic growth by mobilizing more investments, and lifting returns to financial resources, which raises productivity. Relying on provincial panel data from China, this paper attempts to examine if regional productivity growth is accounted for by the deepening process of financial development. Towards this end, an appropriate measurement of financial depth is constructed and then included as a determinant of productivity growth. It finds that a significant and positive nexus exists between financial deepening and productivity growth. Given the divergent pattern of financial deepening between coastal and inland provinces, this finding also helps explain the rising regional disparity in China.
Keywords: N1; O5; 330; growth; financial development; productivity; China; Finanzsektor; Finanzintermediär; Produktivität; China